Coração, juventude e fé: memória e mística da pastoral da juventude do meio popular pjmp na arquidiocese da paraíba (1979-1993) - Nascimento, Edielson Jean da Silva (2009)
This paper is about the Pastoral da Juventude do Meio Popular (PJMP), a catholic pastoral group of Archdiocese of Paraíba formed by folk young people with the aim of discuss youth life and questions. The approach was from the memory interfaces and mystical elements in the genesis and development of this group. The study examines the trajectory of PJMP, between the years 1979 to 1993, emerged as a popular youth movement inside the Catholic Church and its political and social contribution for the education of the young involved; also, it try to understand what is the mystique of PJMP and how it served as encouragement to the struggle of the young, social insertion, and study the relationship (points of tension, conflict, convergence and divergence) between the youth, the pastoral and popular movements as different sectors and at the same time correlated in the organizational structure of the Catholic Church in Paraíba. To do this, we interviewed five former members of PJMP, three members, whose were young militants at the time of the Pastoral searched, and two former aides. The technique used was the oral history, proposed by Meihy; Holanda (2007), and all the analysis was made from the speech of them faced with the existing documentation on the subject. It was concluded that the PJMP in its evangelizing from the reality of oppressed young people, in the light of Liberation Theology and the Renewed Church, was essential to educate the youth about their role in society, through their training and inclusion in a social group that welcomed them and was available to listen, giving them voice and opportunity. It is noticed also that the pastoral group had a Christian activist mystique that made of that young a passionate of the liberating cause of the gospel of Christ, in a critical way, conscious of his status as a creature of God, and therefore possessed of social rights such as housing, education, employment, leisure, and other human needs. At the same time that the action of the young in PJMP was passionate, through its mystique, the way of action was enclosing a militant liberation, not alienating, because inside it that young people was the protagonist of his own story.